Dynamic changes in the human methylome during differentiation - Laurent, Louise; Wong, Eleanor; Li, Guoliang; Huynh, Tien; Tsirigos, Aristotelis; Ong, Chin Thing; Low, Hwee Meng; Kin Sung, Ken Wing; Rigoutsos, Isidore; Loring, Jeanne; Wei, Chia-Lin (Genome Research, 2010)
DNA methylation is a critical epigenetic regulator in mammalian development. Here, we present a whole-genome comparative view of DNA methylation using bisulfite sequencing of three cultured cell types representing progressive stages of differentiation: human embryonic stem cells (hESCs), a fibroblastic differentiated derivative of the hESCs, and neonatal fibroblasts. As a reference, we compared our maps with a methylome map of a fully differentiated adult cell type, mature peripheral blood mononuclear cells (monocytes). We observed many notable common and cell-type-specific features among all cell types. Promoter hypomethylation (both CG and CA) and higher levels of gene body methylation were positively correlated with transcription in all cell types. Exons were more highly methylated than introns, and sharp transitions of methylation occurred at exon–intron boundaries, suggesting a role for differential methylation in transcript splicing. Developmental stage was reflected in both the level of global methylation and extent of non-CpG methylation, with hESC highest, fibroblasts intermediate, and monocytes lowest. Differentiation-associated differential methylation profiles were observed for developmentally regulated genes, including the HOX clusters, other homeobox transcription factors, and pluripotence-associated genes such as POU5F1, TCF3, and KLF4. Our results highlight the value of high-resolution methylation maps, in conjunction with other systems-level analyses, for investigation of previously undetectable developmental regulatory mechanisms.